Pengaruh Pajak Hotel Dan Pajak Hiburan Terhadap Pendapatan Asli Daerah Pemerintah Kota Sukabumi: Studi Kasus pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Kota Sukabumi - Silva Asflara; Idang Nurodin; Hendra Tanjung (AKUNTANSI 45, 2024)
This study aims to determine the effect of hotel tax and entertainment tax on local revenue. The variables used in this study are hotel tax (X1), entertainment tax (X2), and local revenue (Y). The research method used is a quantitative method with an associative approach. The data used is secondary data obtained from the Sukabumi City Regional Revenue and Financial Management Agency Office. The results of research using SPSS 27, show that the effect of Hotel Tax on Regional Original Revenue is tcount 1,105 < ttable 2,014 with a sig value of 0,275> 0,05. While the effect of entertainment tax on local revenue is tcount -0,509 < ttable 2,014 with a sig value of 0,613 > 0,05. The effect of Hotel Tax and Entertainment Tax simultaneously is Fcount 0,665 < Ftable 4,06 with a sig value of 0,520 > 0,05. So it can be concluded that the effect of Hotel Tax and Entertainment Tax partially or simultaneously has no effect and is not significant on Sukabumi City's Local Revenue for the 2018-2022 period, and the coefficient of determination test shows that the contribution of Hotel Tax and Entertainment Tax to Local Revenue is 17,1%, and the rest is influenced by other factors related to the receipt of Local Revenue.